Cell-Penetrating Peptides in Diagnosis and Treatment of Human Diseases: From Preclinical Research to Clinical Application - Xie, Jing; Bi, Ye; Zhang, Huan; Dong, Shiyan; Teng, Lesheng; Lee, Robert J.; Yang, Zhaogang (Frontiers in Pharmacology, 2020)
Cell-penetrating peptides (CPPs) are short peptides (fewer than thirty amino acids) that have been predominantly used in basic and preclinical research during the last thirty years. Since they are not only capable of translocating themselves into cells but also facilitate drug or CPP/cargo complexes to translocate across the plasma membrane, they have potential applications in the disease diagnosis and therapy including cancer, inflammation, central nervous system disorders, otologic and ocular disorders, and diabetes. However, no CPPs or CPP/cargo complexes have been approved by the US Food and Drug Administration (FDA). Many issues should be addressed before translating CPPs into clinics. In this review, we summarize recent developments and innovations in preclinical studies and clinical trials based on using CPP for improved delivery, which have revealed that CPPs or CPP-based delivery systems present outstanding diagnostic therapeutic delivery potential.